Modelo SKOS e ISO 25964: similaridades das recomendações para representação de tesauros - Ferreira, Suelen Camilo (2023)
The Simple Knowledge Organization System (SKOS) data model serves for the availability and interoperable sharing of different types of Knowledge Organization Systems (KOS) in the Web environment. Thesaurus-type KOS play an important role in information retrieval and adhere to the ISO 25964 standard specifically for their construction and mapping. In this scenario, two factors are considered: the SKOS model was already widely used when the ISO 25964 standard emerged, and SKOS recommendations encompass various types of KOS, while ISO 25964 recommendations focus on thesauri. These factors indicate potential similarities between SKOS recommendations and ISO 25964 recommendations. Mapping and analyzing elements that compose the model and the standard contribute to the study and development of thematic representation instruments such as conceptual thesauri. In this context, the objective is to present similarities between the SKOS model and the ISO 25964 standard for the representation of thesauri. This is an exploratory and descriptive research with a qualitative approach, conducted through bibliographic research in national and international databases. The analyzed corpus totaled 25 publications. Eleven categories of similarities between the SKOS model and the ISO 25964 standard for the construction of thesauri were identified and discussed. The results provide theoretical and methodological contributions for the construction, migration, updating, and semantically interoperable maintenance of conceptual thesauri in the Web environment. However, few studies discuss the similarities between the SKOS model and the ISO 25964 standard. Suggestions for future and complementary research are presented.